Association of Risk Factors for Coronary Artery Disease with The Incidence of Abdominal Aortic Calcification On Abdominal CT-Scan Imaging in H. Adam Malik General Hospital - Assania, Rizka Farahin; Daulay, Elvita Rahmi; Refli Hasan (Journal of Society Medicine, 2023)
Introduction: Coronary Artery Disease (CAD) is the one of manifestation for cardiovascular disease and a cause of death and disability. Abdominal aortic calcification (AAC) has been shown to be strongly associated with atherosclerosis and CAD events. This study to investigated the association of risk factors for CAD with the incidence of AAC on abdominal CT Scan. Method: This study was an observational analytic study with a cross-sectional design on 105 patients who underwent abdominal CT scans with/without intravenous contrast at Radiology Department of  H. Adam Malik General Hospital. AAC score was identified calcification on the abdominal aorta (from 1 cm above the origin of the celiac trunk to 1 cm below the iliac bifurcation) use the Agatston method. Analyzing the association CAD risk factors such as gender, age, diabetes mellitus, hypertension, smoking, and alcohol and AAC score. Results: The results of the analysis using the Chi Square comparative test showed that there was a significant relationship between age (p=0.000), hypertension (p=0.017), diabetes (p=0.006), in othe words there is no significant relationship between gender (p = 0.613), smoking (p=0.22) and alcohol (p=0.28) with AAC score. Conclusion: There is a significant relationship between age, hypertension and diabetes with the AAC score.